2017
DOI: 10.1038/cddis.2017.282
|View full text |Cite
|
Sign up to set email alerts
|

AQP9-induced cell cycle arrest is associated with RAS activation and improves chemotherapy treatment efficacy in colorectal cancer

Abstract: Aquaporin-9 (AQP9) expression is associated with arsenic sensitivity in leukemia cells. However, the role of AQP9 in regulating tumor sensitivity to adjuvant chemotherapy in colorectal cancer (CRC) has not been elucidated. In this study, we demonstrated that AQP9 can serve as an independent predictive marker for adjuvant chemotherapy in CRC. Patients with high AQP9 expression had higher rate of disease-free survival (DFS) than those with low AQP9 expression. Upregulation of AQP9 was associated with enhanced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…This was also demonstrated for AQP9, as inward water fluxes weakened membranecytoskeleton anchorage and increased filopodia formation (15,20). Interestingly, despite these functional properties of AQP9, which would suggest an oncogenic effect, AQP9 expression has been found to suppress cancer cell progression (10,18,50). In this study we found that AQP5-expressing MDCK cells displayed unchanged filopodia formation but more dynamic lamellipodia compared with control cells.…”
Section: C658supporting
confidence: 62%
See 1 more Smart Citation
“…This was also demonstrated for AQP9, as inward water fluxes weakened membranecytoskeleton anchorage and increased filopodia formation (15,20). Interestingly, despite these functional properties of AQP9, which would suggest an oncogenic effect, AQP9 expression has been found to suppress cancer cell progression (10,18,50). In this study we found that AQP5-expressing MDCK cells displayed unchanged filopodia formation but more dynamic lamellipodia compared with control cells.…”
Section: C658supporting
confidence: 62%
“…These studies showed that AQP9 expression stimulated cellular filopodia and protrusion formation, structures that enable cell migration. Surprisingly, in contrast to cancer cells expressing AQP5, overexpression of AQP9 in cancer cells decreased EMT and improved cancer treatment (10,18,50).…”
Section: Introductionmentioning
confidence: 93%
“…Huang et al [ 37 ] showed that high expression of AQP9 was correlated with improved disease-free survival (DFS) and increased chemosensitivity in stage III colorectal cancer. Nonetheless, AQP9 mRNA expression and its role in gastric cancer remains to be clarified along with tumor marker and suppression characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that high expression of AQP2 mRNA had no effect on the prognosis of all ovarian cancer patients, serous ovarian cancer patients, as well as in endometrioid ovarian cancer patients. As for AQP9, Huang et al [ 24 ] reported that AQP9 could serve as an independent predictive biomarker for adjuvant chemotherapy, and they demonstrated that high AQP9 expression was related to better disease-free survival in colorectal cancer patients treated with chemotherapy. However, the study of Tan et al [ 25 ] indicated that the expression of both AQP9 mRNA and protein was significantly up-regulated in astrocytic tumors and was positively associated with pathological grade, suggesting that AQP9 might play a critical role in the malignant progression of brain astrocytic tumors.…”
Section: Discussionmentioning
confidence: 99%